The Masquerades of a Childhood Ciliary Body Medulloepithelioma: A Case of Chronic Uveitis, Cataract, and Secondary Glaucoma - Jocelyn Chua; Wisam J. Muen; Ashwin Reddy; John Brookes (Case Reports in Ophthalmological Medicine)
Ciliary body medulloepitheliomas in childhood often masquerade other intraocular conditions due to its insidious nature as well as its secondary effects on proximal intraocular tissues in the anterior chamber. We report a case where a ciliary body medulloepithelioma in a two-year-old boy presents with chronic uveitis, cataract, and an uncontrolled secondary glaucoma after an innocuous blunt ocular trauma. The diagnosis was only made after the occurrence of a ciliary body mass. We discuss the clinical features of ciliary body medulloepitheliomas, the implications of a delayed diagnosis and treatment as well as the concern of periorbital tumor seeding with the use of an aqueous shunt implant in this case.